Urban food systems in Latin America. Territories, mobilities and governance, de Tiana Bakic Hayden y Joaquín Pérez Martín - Flores de la Vega, Margarita (El Colegio de México A.C., 2025)
The text takes a novel approach, engaging in a serious dialogue between urban studies and food studies. It raises methodological issues for research, while also offering reflections on public policy proposals, approaching food in cities as a specific urban problem. The book includes contributions from 25 authors, whose backgrounds span a wide range of disciplines and academic and activist practices, enriching the observations drawn from the case studies.